The Cadherin Superfamily Key Regulators of Animal Development and Physiology - Suzuki, Shintaro T.; Hirano, Shinji (Springer Japan : Imprint: Springer, 2016)
This book presents an overview of the entire field of cadherin research and provides the current basic concept of cadherins. Cadherins have been widely accepted as key regulators of animal development and physiological functions, and it also has become clear that they play essential roles in various human diseases. With contributions by leading scientists, the book covers various aspects of the cadherin superfamily including the history of cadherin research, basic properties of classical cadherins as well as non-classical cadherins, cadherin-associated proteins, and the roles of cadherins in health and diseases. In addition, the book presents some contradictory results and important unanswered questions, and the authors propose their working hypotheses or future directions, to inspire future studies. This volume enables graduate students and young researchers to learn the basics and gain a comprehensive image of the cadherin superfamily, and experts in the field will easily find various topics of interest in relevant areas of study. Additionally, a list of cadherin-related diseases is included for quick reference to cadherins in human diseases.